The molecular, cellular and pathophysiological roles of iRhom pseudoproteases - Dulloo, I; Muliyil, S; Freeman, M (Royal Society, 2019)
iRhom proteins are catalytically inactive relatives of rhomboid intramembrane proteases. There is a rapidly growing body of evidence that these pseudoenzymes have a central function in regulating inflammatory and growth factor signalling and consequent roles in many diseases. iRhom pseudoproteases have evolved new domains from their proteolytic ancestors, which are integral to their modular regulation and functions. Although we cannot yet conclude the full extent of their molecular and cellular mechanisms, there is a clearly emerging theme that they regulate the stability and trafficking of other membrane proteins. In the best understood case, iRhoms act as regulatory cofactors of the ADAM17 protease, controlling its function of shedding cytokines and growth factors. It seems likely that as the involvement of iRhoms in human diseases is increasingly recognized, they will become the focus of pharmaceutical interest, and here we discuss what is known about their molecular mechanisms and relevance in known pathologies.